The Oxford handbook of citizenship / edited by Ayelet Shachar, Rainer Bauböck, Irene Bloemraad, Maarten Vink. - Shachar, Ayelet, 1966-; Bauböck, Rainer; Bloemraad, Irene, 1972-; Vink, Maarten Peter, 1975- (Oxford handbooks., 2017)
Contrary to predictions that it would become increasingly redundant in a globalizing world, citizenship is back with a vengeance. The Oxford Handbook of Citizenship brings together leading experts in law, philosophy, political science, economics, sociology, and geography to provide a multidisciplinary, comparative discussion of different dimensions of citizenship: as legal status and political membership; as rights and obligations; as identity and belonging; as civic virtues and practices of engagement; and as a discourse of political and social equality or responsibility for a common good. The contributors engage with some of the oldest normative and substantive quandaries in the literature, dilemmas that have renewed salience in today's political climate.